Examination of Sexual's Orientation (BDSM) Effects on Depression and Whether Sexual Orientation (BDSM) can Predict the Quality of Life - Louka Penelope; Vorvis Apostolos-Sotirios (2017)
Declaration, Acknowledgements, List of Abbreviations, Abstract, Introduction, Definition and History of BDSM, Researches about BDSM and Psychopathology until the 90's, Aims and Hypotheses of the Present Study, Method, Design, Sample, Materials, Procedure, Results, Discussion, Implications/ Applications, Conclusion, References, Appendices, Application Letter.